Commingling in the Community : album dedicated to Secretary-General of the Caribbean Community, His Excellency Sir Edwin Carrington ([S.l.] [s.n.], 2010)
Photographic album dedicated to Secretary-General of the Caribbean Community, Sir Edwin Carrington.
Keywords: PHOTOGRAPHS